Zn-doped MnO2 ultrathin nanosheets with rich defects for high performance aqueous supercapacitors. (20th June 2022) - Wu, Jianghua; Raza, Waseem; Wang, Peng; Hussain, Arshad; Ding, Yangbin; Yu, Jian; Wu, Yanyan; Zhao, Jie
Highlights: The ultrathin Zn-doped MnO2 nanosheets have been constructed by a one-pot and energy-saving method. This nanosheet presents excellent specific capacitances due to its disordered lattice structure providing active sites for ion storage and transport. The ZnMO electrode presents a high specific capacitance of 392 F g −1 at 1.0 A g −1 . The ZnMO//AC device delivers a high energy density of 55.28 Wh kg −1 at 555.6 W kg −1, and maintains 95.2% capacitance retention after 10, 000 cycles. Abstract: A one-pot and energy-saving method was developed to manufacture defective manganese oxide materials. The insertion of zinc ions improves manganese oxide conductivity results in a significant increase in number of defects in the lattice to provide abundant active sites for energy storage. The synthesized zinc doped manganese oxide achieved a maximum capacity of 392 F g −1 in the three-electrode system, the corresponding supercapacitor reached an outstanding energy density of 55.28 Wh kg −1 at a power density of 555.6 W kg −1, while maintaining 95.2% of the initial capacity after 10, 000 cycles. This research sheds new insights to the preparation of defective materials by a simple one-step method for energy storage applications. Graphical abstract: Image, graphical abstract We have constructed the ultrathin Zn-doped MnO2 nanosheets by a one-pot and energy-saving method, which presents excellent specific capacitances due to its disordered lattice structure providing active sites for ion storage and transport.